2011
DOI: 10.4244/eijv6i7a143
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial progenitor cell capturing stent and short dual antiplatelet therapy in patients on chronic anti-vitamin k regimen undergoing percutaneous coronary interventions: long-term outcomes of a single centre registry

Abstract: Patients on AVK treatment represent a highly comorbid population with a high event rate after PCI. The strategy of PCI with an EPC capture stent and short duration of DAT may be used in patients who need a short-term DAT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…This high rate of MACE has been explained by the high-risk profile of this population, with co-morbid conditions and subsequently high risk of ischemic and bleeding events [10][11][12]. The present sub-analysis from e-SELECT registry confirms this higher rate of MACE in VKA patients as compared to non-VKA patients, further supporting the role of baseline clinical profile (high Charlson index) in determining their worse clinical outcome [9]. It is noteworthy that whereas no differences in MACE or bleeding events were present between the two groups at 1-month follow-up, they became evident at 6 months, suggesting that these events need mid-time follow-up to accrue in patients VKA-treated.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This high rate of MACE has been explained by the high-risk profile of this population, with co-morbid conditions and subsequently high risk of ischemic and bleeding events [10][11][12]. The present sub-analysis from e-SELECT registry confirms this higher rate of MACE in VKA patients as compared to non-VKA patients, further supporting the role of baseline clinical profile (high Charlson index) in determining their worse clinical outcome [9]. It is noteworthy that whereas no differences in MACE or bleeding events were present between the two groups at 1-month follow-up, they became evident at 6 months, suggesting that these events need mid-time follow-up to accrue in patients VKA-treated.…”
Section: Discussionsupporting
confidence: 76%
“…Previous studies in patients with atrial fibrillation under VKA treatment and receiving PCI have shown a MACE rate around 23% and 36% at 1 and 2 years follow-up [7][8][9]. This high rate of MACE has been explained by the high-risk profile of this population, with co-morbid conditions and subsequently high risk of ischemic and bleeding events [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…ECS application only promoted the repair of damaged endothelium, which in turn could prevent in‐stent thrombosis. Studies have shown that for patients with coronary artery diseases who could not tolerate or who were allergic to the long‐term dual antiplatelet drugs, ECS use was a safe and effective treatment method . Therefore, the ECS is a practical choice in patients with coronary artery diseases who cannot take dual antiplatelet drugs for reasons such as a planned surgery in the near future or a coagulation disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who had diabetes (16), dyslipidemia, intractable hypertension coronary heart disease, kidney disease (17), or hemorrhage disease (18) were classified as exclusions. No estrogen or anticoagulant agents were used in either group due to their potential influence on EPC levels (19,20). …”
Section: Methodsmentioning
confidence: 99%